The role of multimerin 1 (MMRN1) in platelet adhesion and characterization of its interactions with fibrillar collagens - Leatherdale, Alexander (My University, 2020)
Multimerin 1 (human: MMRN1, mouse: Mmrn1) is a large homopolymeric glycoprotein that is synthesized and stored by platelets and endothelial cells until activation-induced release. MMRN1 is able to support platelet adhesion through mechanisms involving von Willebrand factor (VWF) and glycoprotein (GP)Ibα, and β3 integrins on activated platelets, and it enhances platelet adhesion to fibrillar collagen, potentially by binding to putative MMRN1-specific GPAGPOGPX (where O is hydroxyproline and X is valine or glutamine) motifs in fibrillar collagens. Using mice with and without selective Mmrn1 deficiency, the goals of this thesis were: 1) further characterize the ability of Mmrn1 to enhance platelet adhesion to collagen, 2) explore the role of fluid shear stress in the ability of Mmrn1 to enhance platelet adhesion, and 3) test the specificity of the GPAGPOGPX motif for Mmrn1 and the ability of GPAGPOGPX to support or enhance platelet adhesion. Mmrn1-deficient (Mmrn1-/-) mouse platelets showed impaired aggregate formation on fibrillar collagen surfaces under high (1500 s-1) and low (300 s-1) shear flow compared to wild-type (Mmrn1+/+) mouse platelets, which was due to reduced initial adhesion and a slower rate of platelet accumulation onto collagen surfaces. Similarly, Mmrn1-/- platelets formed smaller aggregates on immobilized recombinant (r)Vwf surfaces compared to wild-type platelets, and Mmrn1-/- platelets had impaired adhesion and aggregate formation on immobilized murine fibrinogen, but not fibrin, when platelets were pre-activated to release Mmrn1. Type I fibrillar collagen was found to contain a variant of the GPAGPOGPX motif (GPAGPOGPI), and GPAGPOGPX motifs supported adhesion of wild-type, but not Mmrn1-/-, platelets. When presented with the VWF-binding GPRGQOGVMGFO motif and the integrin α2β1-binding GFOGER motif present in fibrillar collagens, the GPAGPOGPX motifs synergistically enhanced platelet adhesion. These findings expand upon the known adhesive functions of platelet multimerin 1 and update knowledge of the motifs that support platelet adhesion to fibrillar collagens.
Keywords: multimerin 1; collagen; platelets; thrombosis; hemostasis; platelet adhesion